The financial resource curse revisited: The supply-side effect of low interest rates - Simon Hildebrandt; Jochen Michaelis (Philipps-University Marburg, School of Business and Economics, 2022)
Benigno and Fornaro (2014) show that an episode of low interest rates may harm an economy. Low interest rates trigger a consumption boom, labor shifts away from the tradable sector, learning spillovers from foreign technology decline and so do domestic total factor productivity, consumption and welfare. In this paper, we show that their conclusion of a financial resource curse does not hold in a world with capital as production factor. Low interest rates now trigger an investment boom, there is no shift of labor between sectors, total factor productivity remains unaffected. Our model confirms "textbook wisdom", i.e., an episode of low interest rates enhances welfare in a small open economy.
Keywords: E22; F36; F43; 330; capital accumulation; endogenous growth; macroeconomic integration